Acute effect of a static- and dynamic-based stretching warm-up on standing long jump performance in primary schoolchildren - Merino-Marban, Rafael; Fuentes, Veronica; Torres, Miriam; Mayorga-Vega, Daniel (Biology of Sport, 2021)
The aim of the present study was to compare the acute effect of a static- vs dynamic-based stretching warm-up on standing long jump (SLJ) performance in primary schoolchildren. The sample was composed of 76 schoolchildren, 43 girls and 33 boys, aged 9–10 years old from three fourth-grade classes of Primary Education. The three groups were cluster-randomly assigned to the control (CG), static (SG) or dynamic (DG) groups. All the schoolchildren performed a standardized warm-up consisting of mobility exercises (five minutes), jogging (five minutes) and the SLJ test. Afterwards the CG schoolchildren received jump theory (eight minutes), the SG performed static stretching (eight minutes) and the DG performed dynamic-bounces stretching (eight minutes). Afterwards, all of them performed the SLJ test again. The results of the one-way ANOVA (F2,73 = 34.184; p < 0.001; η2 p = 0.484), followed by the pairwise comparisons with the Bonferroni adjustment, showed that the DG students (M∆ = 11.07, SE = 1.42) made a significant statistical improvement in their SJL levels compared with the CG (M∆ = -3.00, SE = 1.89; p < 0.001, d = 1.51) and SG students (M∆ = -1.85, SE = 0.67; p 0.05, d = 0.12). The dynamic-bouncing stretch as a final part of a warm-up improves explosive strength performance in primary schoolchildren, and seems to be a good option before carrying out explosive strength activities of the lower body